Investigation of ultrasonification effect on physical and electrical characteristics of Bax Sr1-x TiO3 thin films prepared using sol-gel method - Ruhaizi, Mohd Hatta
The characterization of Barium Strontium Titanate (BST) with the ratio of 60:40 and 80:20 in terms of surface morphology and electrical properties to produce the best BST solution according to its various applications has been done. Properties of Bax Sr1-x TiO3 and the structure of BST capacitor were studied. A (100) oriented p type silicon wafer has been deposited with Platinum (Pt), BST, and Aluminium (Al) in the following order of Si / SiO2 / Pt / BST / Al. The BST was prepared using the chemical solution deposition (CSD) which involved a method called sol-gel which is of interest due to low capital investment cost. The sol-gel method generally uses hydrolytically sensitive metal alkoxides as the starting materials. There were two ways of preparation, namely the sol-gel method with and without involving ultrasonic and both of their results were compared to each other. All the samples have been annealed at 800 oC in oxygen atmosphere. The method for preparation of BST (60/40 and 80/20) was explained in detail and the fabrication process of Bax Sr1-x TiO3 films were described. The samples were tested in two categories, namely surface and electrical characterizations. For surface characterization, X-ray diffraction (XRD) was used to confirm phase formation on the degree texturing. BST formation for every peaks were observed and show the samples were well crystallized for both methods and ratio. Atomic force microscopy (AFM) was used to study the surface morhophology in 2D and 3D topography images. The films for each ratio were very dense, smooth and crack free. With the increment of x value of BST produces larger grain size and the involvement of ultrasonic in te preparation method reduces the grain size. For electrical characterization, semiconductor parameter analyzer (SPA) measured at 100 kHz with the variation of applied voltage ranging from 0V to +5V for current – voltage (I-V) and -8V to +8V for capacitance – voltage (C-V) characteristic for its dielectric properties. Microstructural study of the surface morphology of these samples indicated grains of less than 0.1 μm in size. With the increment of x value of Bax Sr1-x TiO3, the range of the conduction region decreased. The dielectric constant increase proportional to the thickness of BST films. Conclusion is consistent with the result obtained which with involvement of ultrasonic in the preparation steps reduces the grain size and produces smaller dielectric constant and tunability.